Study on the pollution law of complex working conditions in sand-filled fracture well washing operation - Wei Shi; Shifeng Zhang; Dejun Li; Kang Zhang; Xingbang Meng; Qi Yang; Yan Zhuang (PLoS ONE, 2026)
Aiming at the problem of wellbore leakage in the process of sand washing in horizontal wells, this study systematically analyzed the influence of temperature and pressure on the plugging behavior of flushing fluid through the combination of numerical simulation and experimental experiment, and carried out field application. Based on CT technology, the fracture pore structure was reconstructed, and the particle gradation of the well flushing fluid was optimized by combining the Vickers criterion. The particle-fluid interaction model was established by CFD-DEM coupling method. The experimental and simulation results show that the increase of pressure will enhance the sand carrying capacity of fluid, which will lead to the increase of particle invasion depth and aggravate the risk of deep pollution. When the temperature increases, the shallow retention capacity of the particles is enhanced by promoting the thermal expansion of the particles and reducing the viscosity of the well flushing fluid, and the invasion depth is significantly reduced, forming an efficient shallow plugging. The research reveals the law of pressure and temperature on pollution behavior, and provides a theoretical basis for particle system optimization and process parameter design of well washing operation under complex working conditions. The field test shows that the well washing fluid suitable for the formation temperature is optimized, and the construction displacement is reasonably controlled, which can effectively reduce the leakage in the sand washing process and shorten the production recovery period